Manajemen Pembelajaran TPQ Al-Inaroh Bondowoso Dalam Menuntaskan Baca Menulis Dan Meningkatkan Kreativitas Al-Quran - Wahyudi Widodo (Departement of Mathematics Education, 2024)
Taman Pendidikan Al Quran (TPQ) is a non-formal educational facility that aims to improve the ability to read and write the Quran and understanding of Islam. The number of bad records regarding the management of TPQ, as well as the large number of generations of Indonesian Muslims who are illiterate of the Qur'an, seems to be caused by a lack of knowledge of the Qur'an and implementing learning management properly and correctly. This study aims to describe learning management in the Al-Inaroh Bondowoso Qur'an Education Park. This research uses qualitative or field. The results obtained related to learning management at TPQ Al-Inaroh are: Has six elements of management including: People, Money, Materials, Machines, Methods, Markets. The management of TPQ Al-Inaroh Bondowoso in solving illiteracy and developing the creativity of reading the Quran there are four including: 1) careful planning in achieving the Vision and Mission, 2) organizing the distribution of teaching schedules, developing human resources, determining lesson schedules, 3) carrying out greetings, prayers, taking turns forward or discussing, closing prayers, greetings according to the level from kindergarten to above, 4) assessment of achievement books, increase in volume, pre-IMTAS, IMTAS and at the end there will be a graduation and graduation test in general with the community using the Qiraati method.